Clusters and Upgrading: a Purposeful Approach - McDermott, Gerald A.; Rocha Héctor O. (Organizations and Markets in Emerging Economies, 2010)
We develop a theoretical model to investigate how backward societies can improve their upgrading capabilities by transforming existing industrial agglomerations into dynamic clusters. Our main assumptions are two: first, emerging market economies are not uniform but characterized by variety of subnational regional and sectoral organizational and institutional configurations; second, the basic building block and unit of explanation in social sciences is personal action guided by some intention, which is heterogeneous across different actors. Based on these assumptions and the literature on human motives and social networks, we develop a purposeful approach to clusters and upgrading. We argue that governments can develop institutions with private actors that facilitate new types of relationships and improve the access local firms have to a variety of knowledge resources, a key ingredient to upgrading. We illustrate this argument revisiting the literature on clusters and upgrading in Latin America and using two case studies in Argentina, a country better known for its volatility and lack of optimal social capital and institutions. We conclude with avenues for further research.